1993
DOI: 10.1152/ajpregu.1993.264.2.r460
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel angiotensin II receptor involved in angiogenesis in chick embryo chorioallantoic membrane

Abstract: Angiotensin II acts as a growth factor in the cardiovascular system and has been implicated in angiogenesis. The existence of at least two types of angiotensin II receptors, the AT1 and the AT2 receptors, has been suggested by ligand binding studies. We used three different AT receptor antagonists to study the receptor mediating angiotensin II-induced angiogenesis in the chorioallantoic membrane (CAM) of the chick embryo. Angiotensin II caused pronounced angiogenesis of pre- and postcapillary vessels of 30-40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
77
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 0 publications
4
77
0
Order By: Relevance
“…These results are consistent with the physiological and pharmacological studies performed on chicken tissues [10,17,18] or on the cloned receptor in turkey [8]. Also in accordance with these results, Le Noble et al have demonstrated that the angiogenesis in the chorioallantoic membrane of the chicken embryo is stimulated by AnglI and can be inhibited by CGP42112A and not by Dup753 at doses higher than the micromolar [19]. These pharmacological differences suggest that the chicken receptor has a unique structure which contributes to discriminate peptide from non-peptide mamma-lian AnglI receptor antagonists.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with the physiological and pharmacological studies performed on chicken tissues [10,17,18] or on the cloned receptor in turkey [8]. Also in accordance with these results, Le Noble et al have demonstrated that the angiogenesis in the chorioallantoic membrane of the chicken embryo is stimulated by AnglI and can be inhibited by CGP42112A and not by Dup753 at doses higher than the micromolar [19]. These pharmacological differences suggest that the chicken receptor has a unique structure which contributes to discriminate peptide from non-peptide mamma-lian AnglI receptor antagonists.…”
Section: Discussionsupporting
confidence: 88%
“…Besides the well-known effects on vascular tonus, several studies implicate a role of local RAS in oxidative stress defence [33,34] and in the regulation of angiogenesis [35][36][37][38]. To evaluate the effect of islet RAS on the formation of a new islet vascular system after transplantation, losartan was, in some cases, added to the drinking water of newly transplanted animals.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, the renin-angiotensin system (RAS) might be involved in both beneficial angiogenesis and pathological vessel growth. Indeed, the biological active component of RAS, Angiotensin II (Ang II), stimulates endothelial and smooth muscle cells (SMC) proliferation in vitro (Stoll et al, 1995), increases vessel density in rat cremaster muscle (Munzenmaier and Greene, 1996) in the chorioallantoic membrane of the chick embryo (Le Noble et al, 1993), and activates in vivo angiogenesis in the rat subcutaneous sponge granuloma (Walsh et al, 1997). Ang II acts by at least two Ang II receptor subtypes, AT1 and AT2 (Chiu et al, 1989;Timmermans et al, 1993;Whitebread et al, 1989).…”
mentioning
confidence: 99%